The Effectiveness of the ISLAM Model (Integrated Student Life and Akhlak Management) Based on Islamic Values to Shape Religious Character in Elementary School Students - Vika Martahayu; Yopi Malagola (Lembaga Bale Literasi, 2026)
One of the problems with religious character is caused by the student management system that has not yet been managed in an integrated manner. In addition, Islamic religious education in elementary schools still emphasizes knowledge aspects more than the formation of attitudes and behaviors. The purpose of this research is to develop and test the effectiveness of the ISLAM Model (Integrated Student Life and Akhlak Management) based on Islamic values in shaping the religious character of elementary school students. This study employed a quantitative approach using a One-Group Pretest–Posttest Experimental Design to evaluate the effectiveness of the ISLAM Model (Integrated Student Life and Akhlak Management) based on Islamic values in improving the religious character of elementary school students. The subjects of this study are 46 fourth-grade students and 2 teachers at Muhammadiyah Bangka Belitung Elementary School, selected thru purposive sampling. Based on descriptive analysis, there was an increase in the average score from 42.3 on the pretest to 52.1 on the posttest. In addition, the results of the paired sample t-test showed a t-value of -11.3 with p < 0.001, indicating a highly significant difference between the conditions before and after the implementation of the model. The implementation of the ISLAM Model (Integrated Student Life and Akhlak Management) based on Islamic values has proven effective in enhancing the religious character of elementary school students.